Composition of the Essential Oils of Centaurea sericeae Wagenitz and Centaurea ensiformis P.H. Davis from Turkey - Bulent Kose, Y.; Altintas, Ayhan; Tugay, Osman; Uysal, Tuna; Demirci, Betul; Ertugrul, Kuddusi; Husnu Can Baser, K. (Asian Journal of Chemistry, 2010)
The essential oil obtained by hydrodistillation from two endemic Centaurea L. species (Asteraceae); Centaurea sericeae Wagenitz and Centaurea ensiformis P.H. Davis from Turkey was analyzed by gas chromatography (GC) and gas chromatography/mass spectrometry (GC/ MS), simultaneously. Caryophyllene oxide (10.6 %), nonacosane (8.6 %) and hexadecanoic acid (7 %) were the main constituents in the oil of C. sericeae and b-eudesmol (29.8 %), hexadecanoic acid (8 %) and caryophyllene oxide (7.6 %) were the main constituents in the oil of C. ensiformis.